1986
DOI: 10.1093/jn/116.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Copper, Cadmium, Iron, Molybdenum and Manganese on Selenium Utilization by the Rat

Abstract: The possible antagonistic effects of different dietary concentrations of copper (1.3-200 mg/kg), cadmium (1-5 mg/kg), iron (20-500 mg/kg), molybdenum (0.3-50 mg/kg) and manganese (0.2-200 mg/kg) on selenium utilization by the rat were studied by the measurement of the absorption and organ distribution of dietary selenium as [75Se]selenite and by effects on organ glutathione peroxidase (GSH-Px: EC 1.11.1.9) activity. Although a high concentration of copper (200 mg/kg) in the diet did not alter the percentage ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…But no obvious changes were observed in the deposition of Se in testicles in our study. This result agreed with those obtained by White CL and Abdel Rahim AG, who demonstrated that dietary with Cd (1-5 mg/kg diet) and Mo (0.3-50 mg/kg diet) had no significant effects on Se [55,56]. The dosage of Mo and Cd implemented in the experiment was possibly not enough to affect the metabolism of Se.…”
Section: Discussionsupporting
confidence: 92%
“…But no obvious changes were observed in the deposition of Se in testicles in our study. This result agreed with those obtained by White CL and Abdel Rahim AG, who demonstrated that dietary with Cd (1-5 mg/kg diet) and Mo (0.3-50 mg/kg diet) had no significant effects on Se [55,56]. The dosage of Mo and Cd implemented in the experiment was possibly not enough to affect the metabolism of Se.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, no antagonistic effect operated by others minerals could be supposed, considered that their concentrations did not change between experimental groups (Ca and Mg) except for the Fe; however, the levels of the latter, although higher in the SeOL diet, maintain values less than the range of competition (20-500 mg/kg of diet; [43]). In addition, no differences in the plasma profile were found for this mineral.…”
Section: Discussionmentioning
confidence: 97%
“…Selenium consumed in foods exists in a number of organic and inorganic forms, including SeMet (plant and animal sources and supplements), SeCys (mainly animal sources), Se (IV), and Se (VI) (mainly supplements). A body of literature reports that there is no relationship between Se intake and its content in the plasma because this largely depends on the form of Se [41,42] and on the possible antagonistic effects of other mineral compounds [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at optimal seminal plasma concentration, Se was positively correlated to sperm total count, concentration, motility and vitality, and negatively correlated to the biomarker of oxidative stress 8-OHdG [34,113]; however, different studies failed to confirm these correlations [114,115], probably because of different study population or methodology, or because of different ranges of Se detected in the different studies, leading to inconsistencies, due to hormesis mechanism. Few studies attempted to determine the interference between Cd and Se, in animal models; an in vivo study in rats showed that Cd at non toxic but environmentally relevant concentration did not affect Se intestinal absorption or tissue distribution in several organs, including testis, particularly in case of adequate Se dietary supplementation [116]; however, at toxic doses of Cd, a significant decrease in serum concentrations, and an increase in urinary excretion of Se were noted [117]. Conversely, the addition of Se to a diet containing Cd reduced Cd renal excretion, and increased Cd deposition in the testis, although it prevented Cd-induced testis toxicity, by means of the immobilization of Cd in Cd-Se protein complexes [118][119][120][121][122].…”
Section: Interference With Seleniummentioning
confidence: 99%